Community Preparedness for Disasters in Delhi: An Empirical Evaluation - Gautam, Upma; Tewari, Deeksha Bajpai (European Journal of Sustainable Development, 2020)
Background: During a disaster, the community remains the primary and the sole line of response for quite long time period and therefore, incorporating local communities in disaster recovery and risk reduction is crucial, critical component. Aim: Evaluating the vulnerability of a selected society on four aspects: Information, Awareness, Training and Preparedness in a multi hazard prone state of Delhi, India, constitutes the central focal point of this study. Methodology: The data primarily was collected through two separate questionnaires administered to the sample of 726 respondents in the age group of 15 – 75 years. Community was sub-divided into two groups – First included professionals, housewives, retired persons (n= 280) and second included students of school (n=160) and college/university level (n= 286). The sampling technique employed was stratified random with methodology as empirical and analytical. Findings: The study affirms, firstly, that there is lack of awareness of the community about disaster plan, its components and agencies entrusted with disaster planning; secondly, there is a vague understanding about their role both during and post disaster; thirdly, significance of participation in training is also underestimated. Recommendations: A roadmap for increasing resilience of communities through effective training and outreach programs for capacity building up for the ‘whole’ community. Keywords: Disaster risk reduction, community preparedness, resilience, participation, disaster management